HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN PASIEN DALAM MENGKONSUMSI OBAT TUBERKULOSIS PARU DI POLI PARU RUMAH SAKIT UMUM DAERAH M.TH DJAMAN KABUPATEN SANGGAU TAHUN 2024 - Susilawati Susilawati (Scientific Journal of Nursing Research, 2024)
BackgroundThe bacteri a Mycobacterium tuberculosis causes tuberculosis, a chronic infectious disease. Usually, microscopic droplets or droplet nuclei transmit tuberculosis from human to human through the air. It has been known for a long time and continues to be a health problem in various countries around the world.. Objective: to find out the relationship between family support and patient compliance in taking tuberculosis medication at the Pulmonary Polyclinic of RSUD M.Th. Djaman, Sanggau. Method: This study employs a descriptive-quantitative approach, utilizing a cross-sectional research design. This study's sample consisted of all pulmonary tuberculosis patients from the Pulmonary Polyclinic at RSUD M.Th. Djaman, Sanggau, specifically 63 participants. The research employed a total sampling technique, specifically a sample return technique, to sample all members of the population with a count of less than 100. The chi-square test results indicate a significant correlation between information support and patient compliance in taking TB medicine (p-value = 0.002), emotional support for patient compliance in taking TB medicine (p-value = 0.000), instrumental support for patient compliance in taking TB medicine (p-value = 0.000), and support for patient compliance in taking TB medicine (p-value = 0.000), resulting in family support for patient compliance in taking pulmonary TB medicine (p-value = 0.000). Conclusion: Specifically, there is a significant relationship between family support and patient compliance when taking pulmonary TB drugs at the Pulmonary Polyclinic at RSUD M.Th. Djaman, Sanggau. Suggestion: It is hoped that all families of pulmonary TB patients at RSUD M.Th. Djaman, Sanggau to maintain, increase support and create a good environment, so that the level of medication compliance among pulmonary TB patients increases.